FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA INDUSTRI MANUFAKTUR DI BURSA EFEK INDONESIA - FARAH MARGARETHA; ADITYA RIZKY RAMADHAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2010)
The study’s purpose is to acknowledge the factors that influence the company’s capital structure. The samples are manufactures industries in Indonesian Stock Exchange for the period of 2005 up to 2008. Independent variables in this study included size, tangibility, profitability, liquidity, growth, non-debt tax shield, age and investment, whereas dependent variable is capital structure. With using purposive sampling, the total of sample in this study is 40 companies of manufactures industries. Data analysis model is multiple regression. Based on t-test, the results of the size, tangibility, profitability, liquidity, growth, dan age affect the capital structure. But the result of non-debt tax shield and invest-ment has not found significant affect the capital structure. This result indicates that the company’s management has to consider size, tangibility, profitability, liquidity, growth, dan age in capital structure decision.